Determination of permanent establishment in e-commerce: An exploratory study - Othman, Zaleha; Mohd Hanefah, Mustafa; Bidin, Zainol (2005)
Permanent establishment has been used as a principle or threshold to determine whether a country has taxing rights on the business profits of a non-resident taxpayer.That threshold, however, has raised many questions in the context of e-commerce. Many countries are now concerned of how to determine permanent establishment in an e-commerce environment. Some view that the existing rule is insufficient to cope with e-commerce. This is because the existing tax rules were not designed in the era of e-commerce.Tax authorities are also concerned about the tax revenue loss, as there are no specific tax laws relating to permanent establishment in e-commerce. This study was conducted to solicit the perceptions of tax offices and tax practitioners on the criteria used to tax business profits in an e-commerce environment.This paper discusses how permanent establishment is determined in the conventional and e-commerce environments.The findings indicate that the existing tax threshold concerning permanent establishment is applicable in taxing e-commerce business profit, however, further amendments and changes should be incorporated to cater for e-commerce environment.The subjects also perceived that additional criteria should be included in the existing tax laws on permanent establishment to ensure tax treatment on e-commerce do not leave room for tax loss.